ANÁLISES FÍSICO-QUÍMICAS DE IOGURTE ENRIQUECIDO COM EXTRATO DE SOJA - RIGON, ANDRÉIA; RASIA, GISELE M.; LACHNO, IVETE; GHELLAR, RAQUEL F.; KOCH, ROSÂNGELA D. F.; MEIRA, STELA M. M.; VICENZI, RAUL (Salão do Conhecimento, 2013)
Resumo